The Imperial University : Academic Repression and Scholarly Dissent - Chatterjee, Piya, 1965-; Maira, Sunaina, 1969- (University of Minnesota Press, 2014)
The Imperial University brings together scholars to explore the policing of knowledge by explicitly linking the academy to the broader politics of militarism, racism, nationalism, and neoliberalism that define the contemporary imperial state. Based on multidisciplinary research, autobiographical accounts, and even performance scripts, this urgent analysis offers sobering insights into varied manifestations of "the imperial university."